Obtención de plasma rico en plaquetas (PRP) en el Laboratorio de Terapia Celular para uso como herramienta terapéutica en medicina regenerativa - Pérez N, Claudio; Escobar A, Gisselle; Soto B, Pablo; Ibarra C, Camila; Larrondo L, Milton; Alfaro L, Jorge (Revista Hospital Clínico Universidad de Chile, 2021)
Platelet rich plasma (PRP) is used to speed up tissue repair. Despite its widespread use, the therapeutic application of PRP generates controversies in clinical results due to the variability in methods of obtaining the different preparations and differences between the components of different types of PRP, so it’s recommended to mention the type of platelet preparation used. In this article, we describe technical and biologics characteristics of our platelet product, and we compare them to different commercial preparations described in order to validate their clinical use. Our results determine that the preparation can be considered a platelet rich plasma with biological activity in vivo and in vitro, which supports its use as a valid therapeutic tool, alternative to products currently available in Regenerative Medicine.